Cancer patients' experiences with immune checkpoint modulators: A qualitative study. (2nd March 2020) - Ala‐Leppilampi, Kari; Baker, Natalie A.; McKillop, Chris; Butler, Marcus O.; Siu, Lillian L.; Spreafico, Anna; Abdul Razak, Albiruni R.; Joshua, Anthony M.; Hogg, David; Bedard, Philippe L.; Leighl, Natasha; Oza, Amit M.; et al.
Abstract: Background: Minimal qualitative data exist on the experiences of cancer patients treated with immune checkpoint inhibitors or costimulatory antibodies. Understanding the day to day experiences of patients being treated with immune checkpoint modulators, and how these relate to their health‐related quality of life, can inform future research and lead to better clinical decision‐making and care. We report here the first in depth qualitative study to consider patients' diverse and complex experiences with immune checkpoint modulators, with a focus on side effects and how these impact daily life. Methods: This single‐center qualitative study was based on focus groups and semistructured interviews. Patients who were being treated or who had been treated with immune checkpoint modulators within the last year for a range of cancer diagnoses were recruited. Interpretive description informed our inductive, iterative approach to analysis. Results: Eight themes were identified, characterizing the complexity of these patients' lived experiences: major categories of side effects experienced and how they impacted patient well‐being; the heterogeneous nature of side effects experienced; living with uncertainty; reframing the meaning and severity of SEs; focus on survival, hope, and being positive; acceptance and adaptation; feeling supported; and faith in medical innovation. Throughout their accounts, participants highlighted the profound impact that immune checkpoint modulators had on their daily lives. Conclusion: This is the first in‐depth qualitative study into patient accounts of their experiences of treatment with immune checkpoint modulators, related side effects, and how it impacted their daily lives. This research is an integral initial step in developing an instrument that will assess treatment‐related side effects in patients treated with this form of therapy. Abstract : This is the first report of patients' accounts of their experiences with ICM treatment, related SEs, and its impact on daily life. This research is an integral initial step in the development of an instrument that will measure treatment‐related SEs in patients treated with ICMs.